Contralateral surgery in patients scheduled for total thyroidectomy with initial loss or absence of signal during neural monitoring. Issue 4 (25th January 2019) - Sitges‐Serra, A.; Gallego‐Otaegui, L.; Fontané, J.; Trillo, L.; Lorente‐Poch, L.; Sancho, J.
Abstract : Background: Staged total thyroidectomy has been advised to prevent bilateral recurrent laryngeal nerve paralysis when loss of the signal from neural monitoring is observed after dissection of the initial thyroid lobe. This is supported by expert opinion but hard evidence is lacking. A lost signal can return during surgery or, even if it persists, its positive predictive value is only in the range 60–70 per cent. The aim of the present study was to investigate the clinical outcome of patients in whom total thyroidectomy was performed following loss of signal after dissection of the first thyroid lobe. Methods: This was a prospective observational study of adult patients scheduled for neural monitoring during total thyroidectomy. The prevalence of first‐side absence or loss of signal was recorded. The contralateral thyroid lobe was approached routinely. The vagus and recurrent laryngeal nerves on the first side were retested during and at the end of the contralateral procedure. Results: Some 462 patients were included. Loss (32 patients) or initial absence (8) of signal at dissection of the first thyroid lobe was noted in 40 patients (8·7 per cent). Total thyroidectomy was completed in 29 patients, and a change of surgical strategy adopted in 11 patients with benign disease. At retesting, 15 of 37 initially silent nerves recovered electromyographic signal after a mean(s.d.) interval of 30(14) min. Postoperative vocal cord palsy/paresis was demonstrated in 24 of 40 patients. One patient developed a bilateral paresis that could be managed conservatively. Conclusion: After an absence or loss of signal of the recurrent laryngeal nerve following dissection of the first thyroid lobe, contralateral thyroidectomy can be performed safely, avoiding the expense, psychological burden and potential complications of a second procedure. Abstract : Safe when experienced